The Methodology for Strategic Plan Implementation - J. Rojas-Arce (Journal of Applied Research and Technology, 2012)
The objective of this paper is to propose the methodology for the implementation of strategic plans in organizations through the prevention and, in its case, the definition and solution of the problems that frequently affect the implementation processes with many negative manifestations and harmful consequences. By elaborating the concept of implementation under the systems approach and cybernetic paradigm, two types of these problems have been identified: the organizational and the functional ones. The consequent analysis of each kind of them has permitted the development of a methodology for their prevention, identification and solution to assure an effective and efficient implementation process. This methodology consists in realizing five subsequent procedures, which were validated with positive results obtained through their virtual application to the different cases of manifestations with the negative consequences that had occurred during strategic plans implementations described in literature.